Implementasi Project Based Learning untuk Meningkatkan Minat Belajar Siswa di SD 12 Langkai Palangka Raya - Agung Pramana; Yeremia Yeremia; Ryan Fernando; Daniel Np. Simatupang (Jurnal Teologi Injili dan Pendidikan Agama, 2025)
This research aims to increase students' interest in learning through the implementation of a project-based learning model at SD Negeri 12 Langkai. Students' low interest in learning is one of the main obstacles in achieving learning goals, so an approach is needed that is able to create interesting and relevant learning experiences. Project Based Learning is used by integrating real projects that involve students in the learning process actively, from planning to project completion. The learning process is focused on collaboration, exploration and creativity.